Eating habits and hemoglobin level in student - Palma-Lozano, Diana (2019)
Objectives. To identify the relationship between eating habits and hemoglobin level of student nurses at the university of huánuco, in 2017. Methods. It was a transversal study, with a quantitative approach. the population was 913 students, being selected probabilistically and by strata with proportional affiliation a sample of 397. A guide of sociodemographic survey was applied, a questionnaire of eating habits and to measure the level of hemoglobin the hemoglobinometer was used. the chi-square test of independence was used in the inferential analysis. it was considered significant p< 0.05. ethical considerations were taken into account. Results. Analysis of the hemoglobin level of the study sample showed that 7.1% (28) had mild anaemia, compared to a significant proportion who were not anaemic (90.7 % (360)). with regard to eating habits 81.6% (324) had adequate eating habits, compared to 18.4 % (73) with inadequate eating habits. in assessing the relationship between eating habits and hemoglobin level of the study sample, 76.8 % (305) were found to have good eating habits and no anaemia (x2 = 25.28 and p = 0.00), accepting the research hypothesis. Conclusion. Eating habits are significantly related to hemoglobin level in student nurses at the university of Huánuco.